Interdiscursive variations: the literature – theory relation - Gjorgjieva Dimova, Marija (Wydawnictwo Naukowe UAM, 2012)
The subject of this paper is the theoretical fiction genre as a manifestation of interdiscursive relations between fiction and theory/criticism. Firstly, this paper offers a brief overview of the constitutive features of the theoretical fiction genre; and secondly, these features are interpretatively confirmed through the novel Papokot na svetot (Navel of the World) by the Macedonian writer, Venko Andonovski.
Keywords: Interdiscursivity; Novel; Genre hybridization; Fiction-theory